2020
DOI: 10.1101/2020.03.02.973552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant origin determines seed mass, seed nutrients and germination behavior of a dominant grass species

Abstract: 12Although number of studies exploring effects of climate change on plants is increasing, only 13 few studies pay attention to germination. Understanding of germination behaviour is 14 complicated by impact of climate on seed mass and possibly also seed nutrients, which play 15 irreplaceable role in nourishing the sprout. The germination behaviour of species may also 16 depend on trade-off between generative and vegetative reproduction. 17 We studied Festuca rubra originating from localities situated alo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
(14 reference statements)
0
4
0
2
Order By: Relevance
“…For both seed germination and seedling survival, it is also possible that our plants have suffered reduced fitness due to low genetic diversity of the populations or due to poor seed development due to unfavorable conditions at the maternal sites. Both these mechanisms have been previously suggested to affect seed germination and seedling survival (e.g., Dostálek et al, 2010;Münzbergová and Plačková, 2010;Veselá et al, 2020). We, however, assume that the other mechanisms suggested above are more likely as they concern many species and populations.…”
Section: Limitations Of the Studymentioning
confidence: 82%
“…For both seed germination and seedling survival, it is also possible that our plants have suffered reduced fitness due to low genetic diversity of the populations or due to poor seed development due to unfavorable conditions at the maternal sites. Both these mechanisms have been previously suggested to affect seed germination and seedling survival (e.g., Dostálek et al, 2010;Münzbergová and Plačková, 2010;Veselá et al, 2020). We, however, assume that the other mechanisms suggested above are more likely as they concern many species and populations.…”
Section: Limitations Of the Studymentioning
confidence: 82%
“…The effects of temperature and moisture on seed germination may also interact, and the interaction may be more important than either variable alone (e.g., Rivas‐Arancibia et al, 2006; Walck et al, 2011; Gurvich et al, 2017). Most importantly, it has been shown that temperature increase is likely more important for seed germination when coupled with a simultaneous decrease in moisture (Gurvich et al, 2017; Veselá et al, 2020b [Preprint]). There are studies of these interactive effects on germination using species from arid regions (e.g., Rivas‐Arancibia et al, 2006; Gurvich et al, 2017; Flores et al, 2017).…”
mentioning
confidence: 99%
“…There are studies of these interactive effects on germination using species from arid regions (e.g., Rivas‐Arancibia et al, 2006; Gurvich et al, 2017; Flores et al, 2017). To our knowledge, for alpine environments in which a decrease in germination in warm, dry conditions was found, only two such studies exist (Orsenigo et al, 2015; Veselá et al, 2020b [Preprint]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini sejalan dengan pernyataan (Singh et al, 2006) bahwa panjang biji, lebar biji dan berat biji dipengaruhi oleh ketinggian tempat asal benih tersebut. Selanjutnya hasil penelitian (Vesela et al, 2020) bahwa benih yang berasal dari dataran rendah memberikan nilai yang lebih tinggi dan lebih cepat dalam perkecambahan dibandingkan dengan asal benih dataran tinggi, hal ini dapat disebabkan oleh periode vegetasi yang lebih lama di dataran rendah sehingga benih dapat tumbuh dan berkembang dengan baik (Milbau et al, 2009;Meineri et al, 2013).…”
Section: Kecepatan Tumbuh (%/Etmal)unclassified